Wakaf Sukuk – Pembangunan Aset Wakaf Melalui Sukuk Berdasarkan Konsep Istibdal - Mohamad Zaharuddin Zakaria; Ahmad Zaki Salleh; Mushaddad Hasbullah; Abdul Manan Ismail; Mohd Nasir Abd Majid; Nuradli Ridzwan Shah Mohd Dali; Mohd Afiq Ab Jalil (Universiti Sains Islam Malaysia, 2024)
SPECIAL EDITION VOL. 16 NO. 2 Page (152-159)